A new conceptual perspective on circular economy: Preliminarily confirmation of the 7R principle by a descriptive case study in Eastern China - Xing, J.; Silva, J.; Almeida, I. (23rd Congress of the International Sustainable Development Research Society ISDRS, Book of Abstracts, 2017)
The purpose of this study is to outline and demonstrate an innovative conceptual framework on circular economy. Research questions arise from the background literature review and are further developed into the proposed 7R principle model. Its preliminary confirmation is pursued by a descriptive case study of Suzhou Industrial Park (SIP) in Eastern China, which is located neighbouring to Shanghai and extensively recognized as one of the most initial Eco-Industry Parks (EIP) in China and as one of the most successful EIP. To begin with, traditional 3R principle is introduced and, then, the evolvement into 5R is discussed. After that, a proposal for a conceptual framework promoting a 7R principle is put forward. Its components are reduce, reuse, recycle, recover, rethink, resilience and regulate. The descriptive case study based on secondary data provides instances to illustrate that every aspect of the 7R framework is properly embodied by a serial of SIP practices.